IMU- based Determination of Stance Duration During Sprinting. (2016) - Schmidt, Marcus; Rheinländer, Carl; Nolte, Kevin Frederic; Wille, Sebastian; Wehn, Norbert; Jaitner, Thomas
Abstract: Stride parameters like step length, step rate or stance duration during sprinting represent basic and very useful information for track and field coaches. Contact mats or opto- electronic systems like Optojump allow precise and unobtrusive measurements of theses parameters, but their use is limited in space. Inertial measurement units (IMUs) are not bound to these limitations and therefore offer challenging opportunities for in-field diagnosis, especially if combined with wireless data transmission. IMUs have already been used to detect kinematic parameters in track and field but data analysis can typically only be done offline. In this study, we present an IMU-based wearable measurement system for field-based performance analysis and online monitoring, that allows an accurate detection of step parameters in sprinting. Twelve track and field athletes (10 male, 2 female) performed maximal sprints wearing the IMU attached to both ankles. The OptojumpNext photocell system (Microgate, Bolzano, Italy) was used as reference system. Data acquisition rate for both devices was 1000 Hz. Stance durations (tS ) during the phase of maximal velocity are extracted onboard from the accelerometer and gyroscope signal and then sent to an external device. Out of 380 contacts, 364 were detected correctly (96%). tS showed a mean difference of -2.5±4.8ms between OptojumpNext and IMU. Bland-Altman plots derive a 95% limit of agreement (LOA) in the range from 6.8 to -11.8 ms. Hence, the system enables providing reliable and accurate objective real-time feedback for a group of athletes during a training session or competition.